1987
DOI: 10.1007/bf00712760
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin polypeptides expression in different epithelial elements of human salivary glands

Abstract: Immunofluorescent labeling of human salivary glands was carried out with a battery of monoclonal antibodies reactive with specific cytokeratin polypeptides. All the epithelial elements of the glands were positively labelled by a broad-spectrum cytokeratin antibody (KG 8.13) and by antibody Ks 18.18, which reacts with cytokeratin No. 18 exclusively. Labelling of frozen sections with antibody KM 4.62, which is reactive with the 40 Kd (No. 19) cytokeratin, was confined to the ductal system and apparently absent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
2
7

Year Published

1988
1988
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 41 publications
5
51
2
7
Order By: Relevance
“…The histogenesis of salivary pleomorphic adenoma has been studied extensively by both light and electron microscopy (1,(10)(11)(12)(13). At the present time, two major theories have been proposed as to the progenitor cell of origin responsible for cellular FIG (14,18). In the present study , monoclonal antibody K8.12 (nos.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The histogenesis of salivary pleomorphic adenoma has been studied extensively by both light and electron microscopy (1,(10)(11)(12)(13). At the present time, two major theories have been proposed as to the progenitor cell of origin responsible for cellular FIG (14,18). In the present study , monoclonal antibody K8.12 (nos.…”
Section: Discussionmentioning
confidence: 86%
“…The reserve cells located in ductal segments, which specifically reacted for keratin nos. 13 and 16 (K8.12, KS8.55 (14,18)), and LICR-LON-16a (17), might be related to, or coincided with, ductal basal cells, which transform to outer tumor cells. The outer tumor cells of pleomorphic adenomas may originate from ductal basal (reserve) cells, while luminal tumor cells which show an intense staining for PKK1 and KL1, may differentiate from ductal luminal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical identification of keratin proteins in ductal basal cells has reported that strong staining for monoclonal antibody LICR-LON-16a was recognized in those cells (reserve cells) (12). Geiger et al (9) noted that positive reactions with monoclonal anti-keratin antibodies KG8. 13 4,5,6), and with KS858 (nos.…”
Section: Discussionmentioning
confidence: 99%
“…13, 16) existed specifically in ductal basal cells. It has been suggested that basal cells of the salivary gland ducts are the progenitor cells of various tumors, as well as of other proliferative disorders (2,5,6,9,12).…”
Section: Discussionmentioning
confidence: 99%